Importance of pathological review of gestational trophoblastic diseases: results of the Belgian Gestational Trophoblastic Diseases Registry. Issue 6 (29th April 2022) - Schoenen, Sophie; Delbecque, Katty; Van Rompuy, Anne-Sophie; Marbaix, Etienne; Noel, Jean-Christophe; Delvenne, Philippe; Moerman, Philippe; Vergote, Ignace; Kridelka, Frédéric; Vandewal, Aleide; Han, Sileny; Goffin, Frederic
Abstract : Objective: To evaluate the added value of a centralized pathology review of the diagnoses of gestational trophoblastic diseases by expert pathologists and its potential impact on clinical management in a prospective multicenter study based on the Belgian Gestational Trophoblastic Diseases Registry. Methods: From July 2012 to December 2020, the two referral centers of the registry were solicited to advise on 1119 cases. Referral pathologists systematically reviewed all of the initial histological diagnoses. Cases initially assessed by expert pathologists were excluded. A total of 867 files were eligible for the study. Concordance between diagnoses of gestational trophoblastic diseases made by general 'non-expert' and expert pathologists was analyzed together with the potential impact of the alterations on clinical management. Expert pathologists were working in an academic setting with high exposure to placental pathology and national recognition. Results: The rate of discordance between expert and non-expert pathologists for the initial diagnoses was 35%. Almost 95% of complete moles were confirmed by the expert pathologists, but only 61% for partial moles. Compared with previous studies, ancillary techniques (p57 immunohistochemistry, karyotype) were used twice as often by both groups of pathologists in this survey. The diagnosis of gestational trophoblastic neoplasia was altered in 42% of cases. When the initial diagnosis was altered, the clinical relevance of this correction was estimated as down staging, up staging, or not relevant in 65%, 33% and 2% of cases respectively. Conclusion: Systematic centralized pathological review of gestational trophoblastic diseases modified the diagnosis in a third of cases. The results also show that a change in diagnosis would impact clinical management in 98% of patients.